Reinforcement Furudul ‘Ainiyah Santri melalui Intensifikasi Wali Asuh di Pondok Pesantren Nurul Jadid - Abu Hasan Agus R; Firdausul Jannatul Aliah (ISLAMIKA, 2020)
on local wisdom in pesantren. Where guider play have an important figur in providing an understanding of furudhul ‘ainiyah. This observation aims to explore information about reinforcement of santri’s furudhul ‘ainiyah through intensification of guider. This observation uses a qualitative approach to the type of studying case in the Nurul Jadid boarding school, Probolinggo district in the Az-zainiyah zone. The results of this observation there are several strategies wich is undertaken by guider in strengthening (reinforcement) santri’s furudhul ‘ainiyah. First, guider provide guidance to students related to the material furudhul ‘ainiyah. secondly, guider conduct intensive assistance. third, guider evaluate once in a week carried out every Thursday night for santri. therefore, guider the ability and development of santri’s understanding about furudhul ‘ainiyah by individual and conditioning fostering santri’s furudhul ainiyah more organized and more maximal.